Vértices, William Walker filibustero - Duncan Moodie, Quince 1940-; Monestel H., Héctor; Zurita, Pedro (San José, C.R. : Vértices, 1983)
Diálogo entre Guido Saéz (coordinador) Máximo Jeréz, Luis Molina, William Walker, Carmen Lyra acerca de la Guerra de 1856.
Keywords: WALKER, WILLIAM -- 1824-1860; COSTA RICA; HISTORIA; CAMPAÑA NACIONAL, 1856-1857